MODERASI BERAGAMA MENURUT BUYA HAMKA BERDASARKAN Q.S. AL-BAQARAH AYAT 256 - Mutaqin Alzamzami (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Institut Agama Islam Negeri Metro, 2023)
Abstract:This study focuses on the study of surah al-Baqarah: 256 on religious freedom according to Buya Hamka in the interpretation of Al-Azhar by using a content analysis approach. Through this approach, the author tries to describe it analytically and interpretively. And this research method is categorized into a qualitative type, which focuses on literature and library materials as data sources. The results of this study are First, Buya Hamka explained that the verse and the previous verse (Al-Baqarah:255) are closely related and inseparable. He explained that the Verse of The Throne is the most important teaching in Islam which clearly states about monotheism. Second, Buya Hamka in Tafsir al-Azhar explains the verse using the bi al-Ma'śūr method. Third, according to Buya Hamka, based on the Qur'an letter al-Baqarah: 256, that Islam does not allow coercion in embracing religion. But invites people to think about the truth of the message of Islam. For him, coercion in embracing religion makes one's religion false and can cause conflict. The relevance of Buya Hamka's interpretation at this time when viewed from a variety of religions must be maintained in accordance with the struggle of the founding fathers in formulating Pancasila that can embrace all diversity, not by prioritizing egoism. Keywords: Freedom of religion, al-Baqarah verse 256, Buya Hamka.